2021
DOI: 10.1136/bmjopen-2020-045167
|View full text |Cite
|
Sign up to set email alerts
|

Association of adverse childhood experiences with diabetes in adulthood: results of a cross-sectional epidemiological survey in Singapore

Abstract: ObjectivesSeveral studies have linked diabetes mellitus to adverse childhood experiences (ACEs). While a number of studies have examined the association between ACEs and diabetes in Western populations, few have done it in Asian populations. The current study aimed to examine (1) the association between ACEs and diabetes, including the association after age stratification, and (2) the association of comorbid depression, resource use and health-related quality of life (HRQoL) among those with diabetes and ACEs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…Furthermore, Amemiya et al [ 24 ] found that fear of a family member was significantly associated with diabetes in Japan (OR = 1.42, 95% CI = 1.15-1.76), but not in Finland (OR = 1.12, 95% CI = 0.95-1.33). Subramaniam et al [ 29 ] found that the association between bullying and diabetes was not statistically significant (OR = 2.90, 95% CI = 0.70-12.8), whereas Thomas et al [ 30 ] found humiliation was not associated with T2DM (OR = 1.15, 95% CI = 0.74-1.80). Alastalo et al [ 31 ] mentioned that war evacuees and separation from parents were associated with T2DM (OR = 1.40, 95% CI = 1.10-1.90).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Amemiya et al [ 24 ] found that fear of a family member was significantly associated with diabetes in Japan (OR = 1.42, 95% CI = 1.15-1.76), but not in Finland (OR = 1.12, 95% CI = 0.95-1.33). Subramaniam et al [ 29 ] found that the association between bullying and diabetes was not statistically significant (OR = 2.90, 95% CI = 0.70-12.8), whereas Thomas et al [ 30 ] found humiliation was not associated with T2DM (OR = 1.15, 95% CI = 0.74-1.80). Alastalo et al [ 31 ] mentioned that war evacuees and separation from parents were associated with T2DM (OR = 1.40, 95% CI = 1.10-1.90).…”
Section: Resultsmentioning
confidence: 99%
“…However, several properties support its use in the assessment of relative resilience. Specifically, the MCS score is widely used as an indicator of psychological functioning in the general population and has been shown to be negatively associated with the ACE score in various populations, 70–72 as well as in the current study, rendering the regression of ACE on MCS meaningful. As the assessment of relative resilience by the residuals approach is relatively innovative, efforts to standardize its calculation could mitigate some of its limitations and render comparisons across studies easier.…”
Section: Discussionmentioning
confidence: 69%
“…A study conducted in China on middle-aged and old Chinese subjects showed that hunger, unfavored socioeconomic status during childhood, and parental abuse were significantly associated with the development of T2DM and cardiovascular diseases [ 11 ]. Another study conducted in Singapore indicated that childhood emotional neglect, parental separation, divorce, the death of a parent, having one or two ACEs, and young age were significantly associated with higher odds of diabetes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%